Factors Influencing Service User Decision-Making Into Training at Lpk Hikari Kenshu Senta Bantul - Wulandari, Asyora; Soleh, Ahmad; Gayatri, Ida Ayu Er Meytha (Journal of Law, Social Science, and Management Review, 2026)
The purpose of this study was to determine whether cultural, social, personal, and psychological factors influence service user decision-making in choosing LPK Hikari Kenshu Senta Bantul. This research method used quantitative methods, with surveys and questionnaires. The results of the regression analysis show Y ̂ = -7.378 + 0.381 X1 + 0.381 X2 + 0.279 X3 + 0.275 X4 + 4.221. This means that there is a positive influence between cultural factors (X1), social factors (X2), personal factors (X3), and psychological factors (X4) on service user decisions (Y). The value of the coefficient of determination is 0.840. This means that the contribution of cultural factors, social factors, personal factors and psychological factors in influencing service user decision making is 84%, while 16% is influenced by other variables not examined in this study. The results of the t-test at a significance level of 0.05 explain that partially the variables of cultural factors, social factors, personal factors and psychological factors have a significant influence on the variable of service user decision making to attend training at LPK Hikari Kenshu Senta Bantul. The results of the F test at a significance level of 0.05 explain that the variables of cultural factors, social factors, personal factors and psychological factors have a significant influence on the decision-making variables of service users to take training at the LPK Hikari Kenshu Senta Bantul.